2011
DOI: 10.1016/j.jvs.2011.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascularization of shoulder regions of carotid atherosclerotic plaques from patients with diabetes

Abstract: Diabetes was associated with increased vascularization of the shoulder regions in patients with symptomatic carotid atherosclerotic plaques. This was accompanied by increased expression of VEGFR-2. The increased vascularization of the plaque shoulder regions may help explain why patients with diabetes are at increased risk of atherosclerotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This is supported by a recent study using CEUS showing that vascularization of symptomatic plaques seems to be locally increased in the shoulder regions (Saito et al, 2014). In addition, we have previously reported that patients with diabetes have a selective increase in vascularization in the shoulder region of their plaques (Olson et al, 2011). This is in line with the developing consensus on plaque inflammation proposing that inflammation does not dominate the plaque but is abundantly seen in specific critical regions of the plaque such as the shoulder regions (Thim et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is supported by a recent study using CEUS showing that vascularization of symptomatic plaques seems to be locally increased in the shoulder regions (Saito et al, 2014). In addition, we have previously reported that patients with diabetes have a selective increase in vascularization in the shoulder region of their plaques (Olson et al, 2011). This is in line with the developing consensus on plaque inflammation proposing that inflammation does not dominate the plaque but is abundantly seen in specific critical regions of the plaque such as the shoulder regions (Thim et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…It is likely that pathophysiological important vascularization is confined to localized regions within the plaque rather than directly related to the number of vessels. In addition, we have previously reported that patients with diabetes have a selective increase in vascularization in the shoulder region of their plaques (Olson et al, 2011). In addition, we have previously reported that patients with diabetes have a selective increase in vascularization in the shoulder region of their plaques (Olson et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Our histological and in vitro results could explain the link between increased number of microvessels and plaque vulnerability observed in diabetic patients. 31 Hyperglycaemia has been reported to induce abnormal angiogenesis and to promote microangiopathic neovessels in the retina via a VEGF-dependent mechanism, and similar mechanisms might take place in the vascular wall and atherosclerotic plaques. 32 Recent studies indicate that M1 macrophages are predominant in the symptomatic plaques, in particular in vulnerable zones (shoulder regions), while M2 cells dominate within the collagen-rich fibrous cap and adventitia surrounding the plaque, suggesting that plaque instability might be caused by an imbalance between M1 and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Although our observation that contrast uptake was significantly higher in patients with a previous ipsilateral embolic stroke is in agreement with previous reports, 13,16,18 the current analyses and previous reports were done on cross-sectional data and we do not have information on the predictive value of increased contrast uptake. As we have previously shown, vascularisation increases with time after the event and may thus be associated with healing, 24 which complicates interpretation of data. These data should also be interpreted with caution given the low number of observations and the mixed subject group.…”
Section: Limitationsmentioning
confidence: 99%